We Are All Geniuses in Utopia: Towards a Philosophy of Solarpunk - Keenan, Patrick (Univerzita Pardubice, 2024)
In this thesis I will work to create a counter-ideology to capitalist realism by introducing and developing a philosophy of solarpunk. Capitalist Realism is a structure of belief put forward by Mark Fisher which claims that the ideology of capitalism is all-consuming, even affecting our ability to imagine any alternative socioeconomic system. Solarpunk is the banner for a movement originally started in speculative fiction, that explicitly rejects dystopia/dystopian narratives in favor of a sustainable, diverse, and technologically harmonious future. Solarpunk starts with the notion that humanity is perfectly capable of achieving this and although it utilizes present technology in its overall construction, solarpunk does not rely on technology as a necessary condition for achieving this future. It is utopian but not techno-optimistic. It is explicitly anti-capitalist and shares a lineage with both eco-socialism and anarchism, however, solarpunk’s revolution is more ideological, built on practical reform and not creative destruction, utilizing collective action to achieve the alternative. In my construction of a philosophy of solarpunk against this capitalist realism, several distinct concepts are woven together: they are the philosophy of creativity, the role of imagination, the good life, creative computers, automation, and Universal Basic Income.
V utopii jsme všichni géniové: k filosofii solarpunku
Keywords: solarpunk; utopie; kreativita; technologie; umělá inteligence; kapitalismus; kapitalistický realismus; nepodmíněný základní příjem; ideologie; Hannah Arendt; David Graeber; Mark Fisher; Friedrich Nietzsche; solarpunk; utopia; creativity; technology; artificial intelligence; capitalism; capitalist realism; universal basic income; ideology; Hannah Arendt; David Graeber; Mark Fisher; Friedrich Nietzsche